As particularidades da transferência na neurose obsessiva - Rêgo, Mariana Oliveira do (2012)
The transference in obsessional neurosis has many characteristics that can become difficulties in the course of treatment. We intend to analyze the particularities of this transference and relate them to the obsessional neurosis itself. These difficulties in the handle of the obsessional neurosis´s transference emerged from our clinical activity, from which we delimitated our subject. In despite of this, the clinical case that we assisted lacked elements to base a study. We decided then to approach the transference and the obsessional neurosis from a metapshychological point of view, emphasizing the dynamic and economic aspects. Then, we correlated the founded data to the difficulties faced by Freud in his main clinical cases of obsessional neurosis and to the difficulties we faced in the course of the treatment that instigated this study. We concluded that the obsessional neurosis particular form of the repression (the displacement) causes most part of the particularities of this neurosis, like rationalization and ritualistic behavior. The most visible effects of the displacement in the transferencial context are the rationalizations and the resistance to associate freely. These manifestations have relation with the ambivalent type present in obsessive patients. These resistances, as the same time seem to be inoffensive, are very disadvantageous to the treatment, since they prevent the patient of engage the treatment. We concluded that, being an artificial neurosis, the transference should be comprehended in relation of the characteristics of the neurosis in question, since that characteristics are responsible for the transference form and manifestation.